The structures of interstitial hydrogen centers in VO2 in the dilute limit from their vibrational properties and theory. (28th July 2016) - Yin, Weikai; Qin, Ying; Fowler, W Beall; Stavola, Michael; Boatner, Lynn A
Abstract: The introduction of a large concentration of H into VO2 is known to suppress the insulating phase of the metal–insulator transition that occurs upon cooling below 340 K. We have used infrared spectroscopy and complementary theory to study the properties of interstitial H and D in VO2 in the dilute limit to determine the vibrational frequencies, thermal stabilities, and equilibrium positions of isolated interstitial H and D centers. The vibrational lines of several OH and OD centers were observed to have thermal stabilities similar to that of the hydrogen that suppresses the insulating phase. Theory associates two of the four possible OH configurations for Hi in the insulating VO2 monoclinic phase with OH lines seen by experiment. Furthermore, theory predicts the energies and vibrational frequencies for configurations with Hi trapped near a substitutional impurity and suggests such defects as candidates for additional OH centers that have been observed.